RESPON PERTUMBUHAN TANAMAN BLACKBERRY (Rubus sp.) AKIBAT PEMBERIAN PUPUK KANDANG DI TWELVE’S ORGANIC - Andriansyah, Muhammad Afifi; Wijayantiningsih, Sri; Wijayanti, Fitri (Yayasan Education and Social Center, 2024)
Blackberries are the superior commodity cultivated organically in the Twelve's Gardens. This research aims to determine the growth response of Blackberry plants due to the application of manure (goat manure) in Eleven's organic garden. The method used compares two treatments on the same land with different beds. These results were obtained from four weeks of observations, with two treatments in four plots, that were different treatments, each treatment using the same two plots. Treatments for the first two plots are to apply manure evenly, and for the next two beds, there is no manure at all. That observation aims to determine the growth response of the Blackberry plant, due to the application of manure (goat manure) in the Twelve's Organic Garden. Apart from that, observations were done to see the comparisons of plant growth given manure and without manure through production results. Providing manure (goat) at a dose of 25kg/24 greatly influenced the growth response of blackberry plants in B1 and B2 with condition plant height, number of leaves, and number of new shoots. The treatment of providing goat manure on blackberry plants resulted in a greater growth in the number of leaves compared to the treatment without fertilization using goat manure